Ad

...67 A. **3X**+(-1.67)=2 **3X**-1.67=2 **3X**=2+1.67 **3X**=3.67 X=3.67/3 X=1.22 (**3x**-2y)2 = **2x**=4 **3x**+y=2;**2x**-y sol'n: **3x**+y=2 y=**2x**-3 **3x**+**2x**-3=2 5x\5=2+3\5 x=1 3(1)+y=2 3+y=2 y=2-3 y=-1 ans.x=1;y=-1 ...

Ad

3*10 - 13 = 17) Let x=Ruel's age now, and **2x**=Edwin's age now. **2x**+3=3(x+3)-13 **2x**+3=**3x**+9-13 **2x**+3=**3x**-4 **2x**+7=**3x** 7=x If you are going to post these, the least you could do is rate them as Fixya. :-) Thanks

Ad

Question about Excel@ Mathematics Study Skills (71101) for PC, Mac

...**2X**+X)]=1/2[cos(X)-cos(**3X**)] then calculated the derivative of 29/2*[cos(X)-cos(**3X**)] which is 29/2*[-si(X) +3*sin(**3X**)] The challenge for you is to prove that the two forms are equivalent ...

Question about Excel@ Mathematics Study Skills (71101) for PC, Mac

**2x**-1/5-**3x**/7+2=x+9/2-x-3/10 Numerical equations with fractions Hi, **2x** - 1/5 - **3x**/7 + 2 = x + 9/2 - x - 3/10 Or, **2x** - **3x**/7 = 1/5 - 2 + 9/2 - 3/10 Or, (14x + 3)/7 = (2 - 20 + 45 - 3)/10 Or, 11x/7 = 24/10

...**2x**+3y)(**3x**+2y) (**2x** - 3y)(**3x** + 2y) = **2x*****3x** + **2x***2y - 3y***3x** - 3y*2y = 6x^2 + 4xy - 9xy - 6y^2 = 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set ...

**2x**^5+4x^4-**3x**^2+7,7x^4-**3x**^3+x^2-9 5x -2(x-2) = 6 -2(-**3x**-3) 5x -**2x** +4 = 6 +6x +6 (use the distributive property) **3x** + 4 = 6x + 12 (collect terms) 4 = **3x** + 12 (subtract **3x** from both sides to get all x on

...6-**2x**+2y=**3x**+5 Get the constant terms on the left and the variable ones on the right 6-5=**3x**+**2x**-2y or 1=5x-2y. I prefer to have the variables on the left, so I swap left and right 5x-2y=1 or ...

Question about Racing Ion Motorcycle Jersey 2010

**3x** - 19 = **2x** + 2 Put all the constants on one side by adding 19 to both sides. **3x** - 19 +19= **2x** + 2 + 19 **3x** = **2x** +21 Subtract **2x** from both sides to have all the x's on one side. **3x** - **2x** = **2x** +21 - **2x** x

...**3x**) = **2x** -**3x** - -**3x** = 0 The equation then becomes **2x**=10 **2x**/2 = x and 10/2 =5 then x=5. does it work 5x5=10+3*5 YES x=1.25 5x=10-**3x** (Add **3x** to both sides) 8x=10 (Divide 8 from both sides) x=1.25 (Now ...

...= log(**2x** + 3/4) log(3/4*x^2) = log(**2x** + 3/4) 3/4*x^2 = **2x** + 3/4 multiply equation by 4: **3x**^2 = 8x + 3 **3x**^2 - 8x - 3 = 0 solve this quadratic eq. and you get x1 = 3 x2 = -1/3 does it make

Usually answered in minutes!

19,213 Questions

12,350 Questions

7,428 Questions

7,325 Questions

5,424 Questions